Mergers and Acquisitions: Analysis of Effects on Shareholder Value - Zhang, Xiya (2013)
Mergers and acquisitions (M&As) are regarded as a good strategy for companies to expand their scale and make more profits and then become increasingly popular around the global market nowadays. Importantly, mergers and acquisitions not only have the effect on the performance of acquiring and target companies but also create a beneficial or adverse effect on the shareholder of acquiring and target companies. This dissertation is aimed at analyzing the impact of mergers and acquisitions on shareholder’s wealth after the announcement of M&As. The main methodology is used by an event study and the data involves 120 deals (i.e. 120 acquiring companies in UK and 120 target companies in local countries and foreign countries) in mergers and acquisitions from year 2000 to year 2009. This study picks up two event dates (from t=-10 to t=10 and from t=-10 to t=30) in order to observe thoroughly the effect of the announcement of M&As. Furthermore, the average abnormal return (AAR) and cumulative abnormal return (CAAR) are two vital variables and this study focus on the movements of AAR and CAAR before and after the announcement date.